The Impact of Multisector Intervention to Accelerate Derivation of Child Stunting: A Systematic Review - Syakur, Rosdiana (Universitas Muslim Indonesia, 2023)
Stunting is considered a major concern for children worldwide in public health. Around 149 million children under the age of 5 were affected by stunting in 2018. The purpose of this article is to evaluated health and nutrition programs to identify context-specific intervention packages that may help prioritize the implementation of stunting programs. Methods: Using electronic databases, the literature published between 2009 and 2019 was systematically reviewed, It identified programs in which nutrition-specific and nutrition-sensitive interventions for children under 5 years of age were implemented. Results: 11 programmes identified where nutrition specific and sensitive approaches had been implemented, Nutrition education and counseling, growth monitoring and promotion, immunization, water, sanitation and hygiene, and social security networks were the most common interventions. Conclusions: Programs combining nutrition-specific and nutrition-sensitive interventions, especially those with strong access to health and safety net components, are most effective in reducing stunting.